2020
DOI: 10.1161/circep.119.008267
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Bundle Branch Area Pacing to Achieve Physiological Conduction System Activation

Abstract: Background - Left bundle branch pacing (LBBP) is a technique for conduction system pacing, but it often results in right bundle branch block (RBBB) morphology on the electrocardiogram. This study was designed to assess simultaneous pacing of the left and right bundle branch areas to achieve more synchronous ventricular activation. Methods - In symptomatic bradycardia patients, the distal electrode of a bipolar pacing lead was placed at the left bundle b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
1
25
0
1
Order By: Relevance
“…The reason may be that when LBBP paces the left conduction system, the impulse is rapidly retrograde along HIS to the right bundle branch, 17–19 and slowly transversely across the interventricular septum to the right bundle branch 20 . Recently, Chen et al 21 . reported bilateral bundle branch pacing (BBBP), the results showed that BBBP could achieve more synchronous ventricular activation than LBBP, but its efficacy and safety needed to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be that when LBBP paces the left conduction system, the impulse is rapidly retrograde along HIS to the right bundle branch, 17–19 and slowly transversely across the interventricular septum to the right bundle branch 20 . Recently, Chen et al 21 . reported bilateral bundle branch pacing (BBBP), the results showed that BBBP could achieve more synchronous ventricular activation than LBBP, but its efficacy and safety needed to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…One of specific features of LBBP are right bundle branch block (RBBB) paced QRS morphology, which may have an effect on right ventricular conduction and adverse consequences. However, RBBB could be eliminated by adjusting AV delay 9 (fused with intrinsic activation from the right bundle branch), combination with left ventricular epicardial pacing or bilateral bundle branch area pacing 25 (the potentiality of the ring electrode capture on the right side of the interventricular septum, the transverse interconnections, 26 or virtual field stimulation 27,28 ). Second, due to deep position in the basal interventricular septum of the pacing lead, there are some concerns about LBBP: (1) coronary artery damage 29,30 ; (2) lead stability affected by constant contraction of septal myocardium; (3) progress of hypertrophic and fibrotic interventricular septum which may preclude the successful capture of LBBP.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have also suggested that LBBP might be a viable choice to correct the RBBB ( 24 , 25 ). Lin et al ( 26 ) employed unipolar LBBP to shorten the RBBB duration from 137.7 ± 19.2 ms to 118.7 ± 6.7 ms, and bipolar LBBP to shorten the RBBB duration even further to 105.0 ± 5.0 ms, eliminating interventricular conduction delay. Previous studies have also shown that LBBP can shorten the QRS duration of intrinsic RBBB by about 30ms ( 27 ), as summarized in Table 1 .…”
Section: Left Bundle Branch Pacing In Right Bundle Branch Block Patientsmentioning
confidence: 99%